Pengaruh Terapi Bermain Continueing Story Terhadap Kecerdasan Jamak Pada Anak Prasekolah - Hindyah Ike Suhariati; Endang Yuswatiningsih (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
Intelligence is the highest ability possessed by humans. The purpose of this research is to analyze the effect of play continuing story therapy on plural intelligence in preschool children at TK DWP 2 Lawang General Hospital. The design in this study was Quasi Experiment (Pre and Post-test nonequivalent control group). The affordable population is all pre-school age children in Dharma Wanita Persatuan 2 Kindergarten Dr. Radjiman Wediodiningrat Lawang Malang Malang East Java who have problems with multiple intelligence problems as many as 45 children, the sample in this study amounted to 32 children. Analysis of paired data (pre and post-test) on the multiple intelligence variable used the Wilcoxon sign rank test. Mann Whitney Test to test the differences in plural intelligence in the control group and the treatment group after giving treatment. If the statistical test results obtained p <0.05, then H1 is accepted, it means the research hypothesis is accepted. The results showed play stimulation Continuing Story increased plural intelligence in pre-school age children in TK Dharma Wanita Persatuan 2 RSJ Dr. Radjiman Wediodiningrat Lawang (treatment group) p-value = 0,000, Play activities according to the curriculum at school increased plural intelligence in preschool-age children Dharma Wanita TK Kindergarten Unity 2 RSJ Dr. Radjiman Wediodiningrat Lawang (control group) p-value = 0.007, Plural Intelligence Improvement with play stimulation Continuing Story is higher than the play activities according to the curriculum in the Mann-Whitney Test school p-value = 0,000. This research concludes that there is an effect of play therapy continuing story on plural intelligence in preschool children in TKP DWP 2 RSJ Lawang.